Skin-related adverse events and their associated factors among Diabetic patients on insulin therapy - Dennis Patson Mbwambo; Wigilya Mikomangwa; Rajabu Hussein Mkugwe; Bertha Mallya; Manase Kilonzi; Method Kazaura; Magreth Angelus; Kaushik Ramaiya; Mary Mayige; Ritah Mutagonda; Alphonce Ignace Marealle (PLoS ONE, 2026)
Background More than 530 million individuals globally are afflicted with diabetes mellitus (DM), and the prevalence continues to escalate. Insulin remains the cornerstone of DM management across the globe. Nevertheless, existing literature indicates that individuals utilizing insulin are susceptible to developing abscesses and scar formation at injection sites. These complications may undermine therapeutic adherence, thereby adversely impacting the intended clinical outcomes. This study aimed to evaluate the prevalence of abscesses and scar formation at injection sites, along with their associated factors, among diabetic patients undergoing insulin therapy in Dar es Salaam, Tanzania. Methods A hospital-based analytical cross-sectional study was conducted from the 28th of February 2024 to the 25th of May 2024. A total of 428 patients diagnosed with diabetes mellitus and undergoing insulin therapy were enrolled from four selected hospitals in Dar es Salaam. A validated case report form (CRF) was employed to gather socio-demographic characteristics and clinical data pertinent to the formation of abscesses and scars following insulin therapy. Data were analyzed utilizing Stata version 15.0 software, with findings summarized as frequencies and percentages. Factors associated with the development of abscesses and scarring were evaluated using modified Poisson regression, and a p-value of less than 0.05 was deemed statistically significant. Results Of 428 participants, the prevalence of abscesses and scar formation at the insulin injection site was 22.2% and 46.7%, respectively. Factors positively associated with abscesses were improper injection technique (adjusted Prevalence Ratio [aPR] = 1.11; 95% CI: 1.02–1.21, p = 0.009) and poor injection site rotation (aPR = 2.7; 95% CI: 1.13–6.45, p = 0.025). In contrast, the use of an insulin pen was negatively associated with abscesses (aPR = 0.13; 95% CI: 0.04–0.48, p = 0.002). Scar formation was positively associated with improper injection site rotation (aPR = 1.63; 95% CI: 1.03–2.32, p = 0.037) and uncontrolled blood glucose levels (aPR = 1.69; 95% CI: 1.01–2.84, p = 0.049). Conclusion This study indicates that skin complications at insulin injection sites are highly prevalent. The findings suggest that improper injection technique, poor site rotation, and uncontrolled blood glucose are significant modifiable risk factors. The use of insulin pens may help reduce the risk of abscesses. Therefore, targeted patient education on correct injection practices and glycemic control is crucial to minimize these complications.